FORMATION OF THE MECHANISM FOR ENSURING ECONOMIC SECURITY OF THE ENTERPRISE CONSIDERING RESOURCE MANAGEMENT PROCESSES IN CRISIS CONDITIONS - KRYVDYK, Mykhailo; RUDNICHENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the issue of ensuring the economic security of industrial enterprises in an unstable economic environment caused by military actions in Ukraine. The strategic importance of economic security for enterprises operating under crisis conditions is identified, and the necessity of integrating it into resource management processes is substantiated. Existing scientific approaches to the problem of organizational and economic security assurance are analyzed, and unresolved aspects requiring further research are highlighted. The main objective of the study is to develop a mechanism for ensuring the economic security of an industrial enterprise, taking into account resource management processes, which will contribute to enhancing its resilience and competitiveness. The proposed mechanism integrates organizational and economic aspects, ensuring the incorporation of security measures into the enterprise management system at strategic, tactical, and operational levels. Key internal and external environmental factors affecting the level of economic security are identified, and the fundamental principles, functions, and operational modes of the security mechanism are examined. The research findings can be applied in the practical activities of enterprises to improve resource management efficiency and minimize threats in crisis conditions.